EMISI GAS KARBON DIOKSIDA (CO2) PADA PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq) YANG DITUMPANGSARI DENGAN TANAMAN PANGAN DI LAHAN GAMBUT - Muhammad Ridha Pahlipi; Ervina Aryanti; Mokhamad Irfan; Indah Permanasari; Ahmad Taufiq Arminudin (Jurnal Agroteknologi, 2017)
Peat land conversion into oil palm plantations leads was increased emissions of carbon dioxide (CO2). Plants on peat land and environmental conditions believed to be factors in the emission of carbon dioxide (CO2). The porpuse of this research was determined the emissions of carbon dioxide (CO2) in oil palm plantations are intercropped with cropping crop on peat land and the influence of environmental factors on the emission of carbon dioxide (CO2). This research was conducted in September 2015 until April 2016 in Rimbo Panjang village, Subdiscrict Tambang, District of Kampar, Province of Riau. Cropping crop used were corn and soybeans. The method used in this study was a Random Block Design with four treatments and four replications. The treatments were palm - berau, palm oil - corn, palm oil - soybean, palm oil – intercropping (soybean – maize). Parameters measured were carbon dioxide (CO2), soil temperature, air temperature, the temperature of the lid, the depth of the water table and soil pH. The results showed that carbon dioxide emissions (CO2) in oil palm plantations are intercropped with cropping crop (corn and soybeans) were not significantly different. The influence of air temperature, soil temperature, the temperature of the lid, and the depth of the ground water level were inversely and  insignificant to the emission of carbon dioxide (CO2). As for getting nearly neutral pH, the emission of carbon dioxide (CO2) is increasing, but insignificant.